2017
DOI: 10.3892/etm.2017.4402
|View full text |Cite
|
Sign up to set email alerts
|

Berberine alleviates dextran sodium sulfate-induced colitis by improving intestinal barrier function and reducing inflammation and oxidative stress

Abstract: Berberine has demonstrated efficacy in alleviating experimental colitis in vivo and in vitro. However, the anti-colitis mechanisms of berberine that enable it to promote intestinal barrier function in vivo remain unclear. The present study aimed to evaluate the effect of berberine on intestinal epithelial barrier function, expression of tight junction proteins and the levels of inflammatory and oxidative stress factors in the intestinal mucosa of dextran sulfate sodium (DSS)-induced colitis mice. Berberine (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…UC manifested as an idiopathic, relapsing and etiologically complicated inflammatory disorder, involving the interaction between environment factors, genetic emotivity, perturbation of immune homeostasis, and dysfunction of intestinal mucosal barrier 5,6,18 . Over the past decades, oral administration of berberine has been demonstrated to exert protective capacity on DSSinduced experimental acute UC, which dominantly attributed to the critical role of berberine in modulating the inflammatory responses from immune cell and epithelial cells, maintaining the intestinal barrier function, and regulating gut microbiota 24,41,42 . Besides, berberine could also attenuate colonic macromorphological and histopathological inflammation through suppressing the expansion and overaction of Th17 cells in DSS-induced murine chronic UC 43,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UC manifested as an idiopathic, relapsing and etiologically complicated inflammatory disorder, involving the interaction between environment factors, genetic emotivity, perturbation of immune homeostasis, and dysfunction of intestinal mucosal barrier 5,6,18 . Over the past decades, oral administration of berberine has been demonstrated to exert protective capacity on DSSinduced experimental acute UC, which dominantly attributed to the critical role of berberine in modulating the inflammatory responses from immune cell and epithelial cells, maintaining the intestinal barrier function, and regulating gut microbiota 24,41,42 . Besides, berberine could also attenuate colonic macromorphological and histopathological inflammation through suppressing the expansion and overaction of Th17 cells in DSS-induced murine chronic UC 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that berberine possessed numerous pharmacological activities, including anti-microbial, anti-diabetic, anti-colorectal cancer, analgesic, lipid modulatory, anti-depressant, and blood glucose and anti-inflammatory effects 21 . Particularly, berberine has been suggested to function as an effective agent in treating experimental colitis, including UC and CD, which were largely due to the role of berberine in modulating gut microbiota, neurogenic inflammation, mucosal immunity, and barrier function 20,[22][23][24] . Though the underlying mechanism of berberine has been focused on activation of adenosine 5′-monophosphate (AMP)activated protein kinase (AMPK) 23 , we revealed a new molecular mechanism of berberine in attenuating chronic UC.…”
Section: Introductionmentioning
confidence: 99%
“…As a main ingredient of C. chinensis Franch., berberine (100 mg/kg) treatment inhibits the activations of NF-κB and mitogen-activated protein kinase (MAPK), which contributes to down-regulation of tumor necrosis factor (TNF), interferon gamma (IFN-γ) and IL-17 expressions in colonic macrophages and epithelial cells from DSS-induced mice, showing the reductions of crypt injury and severe inflammatory damage [50]. In addition, berberine (100 mg/kg or 100 μM) treatment improves intestinal barrier function through suppression of the phosphorylated colonic signal transducer and activator of transcription (STAT) 3 and myosin light chain (MLC) kinase-MLC signaling pathway, as well as inhibition of IFN-γ and TNF-α expressions and macrophage infiltration into the intestinal mucosa in DSS-colitis mice [51,52].…”
Section: Heat-clearing and Dampness-drying Medicinementioning
confidence: 99%
“…Unfortunately, no particular effective clinical treatment is reported because of undefined pathogenesis. Notably, the chemical components of traditional Chinese medicine, including baicalin [25], curcumin [26], berberine [27], oxymatrine [28], and astragalus polysaccharides [29], have shown significant progress in UC treatment. In addition, some studies have focused on the improvement of UC by using dietary supplements (e.g., anthocyanins, flavan-3-ols and green tea, proanthocyanidins and cocoa, isoflavones and soy, flavonols, gingerols and ginger, and hydroxycinnamic acids), nutraceutical supplements (e.g., prebiotics, probiotics, synbiotics, and fish oil), and other natural compounds in recent years [30][31][32].…”
Section: Discussionmentioning
confidence: 99%